Emphysematous Pyelonephritis: Radiological Perspective (Bangladesh Journal of Medical Science, 2013)
Emphysematous pyelonephritis (EPN) is an acute necrotizing parenchymal and perirenal infection and is caused by gas-forming organisms. Diabetes mellitus and ureteric obstruction are the predisposing factors for EPN. Computerized tomography (CT) scan is the modality of choice in diagnosing the disease, determining the extent of infection and helps in management. We report a case of emphysematous pyelonephritis in 52 years old man with emphasis on plain radiographic and CT scan findings. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13358 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.93-95